The Capability of Humanskill of the Madrassa Principal Leadership in Managing Human Resources in MAN 2 West Aceh - Herman, Herman; Kurniawan, Ade; Idris, Jamaluddin (SCAD Independent, 2023)
The management of education units needs the human skills of madrasah principal leadership in organizing, mobilizing, and motivating human resources (HR). The purpose of this study was to assess madrasah leadership's human capability in managing human resources at a senior high school in West Aceh. This study used a qualitative method with an interactive naturalistic approach in analyzing the human skill capability of the madrasah principal in managing human resources. Data collection methods were through observation, structured interviews and document studies on reports of intra and extracurricular activities in madrasah. The results showed that the human skill capability of the madrasah principal leadership in managing human resources was well categorized, except for some aspects that were still weak and needed to be improved. First, the capability to cooperate included assisting and helping others, providing opportunities for innovation, and taking policies that benefited the madrasah apparatus. Second, the capabilities to build solid teamwork, including harmonious working relationships, maintaining mutual manners and rules, and smooth communication .Third, the capability to be empathetic included maintaining mutual feelings, being calm and comfortable, and building a bright future.